Lead-free tin-based perovskites nanocrystals for high-performance self-driven bulk-heterojunction photodetectors. (October 2022) - Sulaman, M.; Yang, S.Y.; Zhang, Z.H.; Imran, A.; Bukhtiar, A.; Ge, Z.H.; Tang, Y.; Jiang, Y.R.; Tang, L.B.; Zou, B.S.
Abstract: Currently, photodetectors based on metal-halide perovskites are the fastest-emergent photovoltaics technology in terms of research and development. Lead-based perovskite semiconductors exhibit unusual structural and electrical properties due to the chemical instability of Pb +2 content. All-inorganic lead-free perovskites have become an alternative perovskite material for optoelectronic devices. However, high trap state density and the surface non-uniformity of the active layer make them inappropriate for high-performance photodetectors. Therefore, in this work, a feasible method for surface-passivation of all-inorganic lead-free perovskites with poly (3-hexylthiophene) (P3HT) as the photoactive layer for high-performance photodetectors is presented, and the underlain mechanisms to enhance device performance are investigated by experiments and simulation. As the result, the photoresponsivity of 1.56 A/W with a specific detectivity of 1.40 × 10 14 Jones was obtained from photodetectors ITO/ZnO/CsSnBr3 :P3HT/CuSCN/Au under 0.1 mW/cm 2 532 nm illumination in self-driven mode. Our experiments and simulation show that the enhanced-performance origins from both the enhanced transportation of the photogenerated charge carriers and the suppressed dark current through the device. Graphical abstract: In this paper, airs-stable lead-free CsSnBr3 NCs blended with P3HT as the photoactive layer for high-performance photodetectors ITO/ZnO/CsSnBr3 :P3HT/CuSCN/Au are presented, the underlain mechanisms for enhanced performance are investigated by simulation, confirming it origins from both the enhanced transportation of charge carriers and the suppressed dark current through the device. Image 1 Highlights: All-inorganic lead-free CsSnBr3 perovskites are synthesized by Tip-ultrasonication method. A feasible method for surface-passivation of CsSnBr3 blended with P3HT as the photoactive layer is presented. Underlain mechanisms for enhanced device performance are studied by experiments and simulation. High R of 1.56 A/W with a D * of 1.40 × 10 14 Jones was obtained for the self-powered photodetector.